Basalt‐seawater interaction, the Plenus Cold Event, enhanced weathering and geochemical change: deconstructing Oceanic Anoxic Event 2 (Cenomanian–Turonian, Late Cretaceous). Issue 1 (28th October 2016) - Jenkyns, Hugh C.; Dickson, Alexander J.; Ruhl, Micha; van den Boorn, Sander H. J. M.
Abstract: Oceanic Anoxic Event 2 (Cenomanian–Turonian: ca 94 Ma) represents a major palaeoceanographic phenomenon that took place during an interval of extreme global warmth when large amounts of organic matter entered the marine burial record, probably triggered by increased availability of nutrients for planktonic biota. Three sections (Eastbourne, Sussex, UK; Raia del Pedale, Campania, Italy; and Tarfaya, Morocco) recording this event illustrate the influence on marine geochemistry of mafic volcanic rock‐seawater interaction, anoxia to euxinia, and re‐oxygenation and cooling during the so‐called 'Plenus Cold Event'. The Eastbourne section represents the organic‐lean epicontinental pelagic deposits of the English Chalk; the Raia del Pedale section represents a shallow‐water platform carbonate on the Tethyan continental margin, also largely devoid of organic matter; and the Tarfaya core represents an Atlantic margin site where cyclically bedded organic‐rich sediments were well developed. Correlation between all three sections is readily achieved by biostratigraphy and carbon‐isotope stratigraphy (δ 13 Ccarb and δ 13 Corg ) over the Oceanic Anoxic Event 2 interval, represented by a characteristic broad positive carbon‐isotope excursion. The stratigraphic range of the Plenus Cold Event, defined by the presence, in two discrete levels, of boreal fauna and an excursion to heavier oxygen‐isotope values in the English Chalk, can be identified in Raia del Pedale and Tarfaya by using the carbon‐isotope curve as a correlative tool. Similarly, a section in southern France allows its co‐existing osmium‐isotope excursion to relatively unradiogenic values to be placed in the context of the Oceanic Anoxic Event in all three analysed sections. A fall to lower osmium‐isotope values clearly pre‐dated the onset of Oceanic Anoxic Event 2, as defined by the initial rise in carbon‐isotope values, allowing the putative magmatic/mafic event as a trigger for the Oceanic Anoxic Event. An initial drop in sulphur‐isotope ratios (δ 34 S CAS ) at Eastbourne correlates with the osmium‐isotope curve, suggesting that isotopically light sulphur could have been derived from a mafic igneous source. Re‐oxygenation of sediments of all three investigated sections during the Plenus Cold Event is variably illustrated by change in cerium:calcium, iodine:calcium, molybedenum:calcium and uranium:calcium ratios, according to the redox behaviour of the elements in question and whether controls on seawater chemistry were local or global in nature. Changes in molybdenum‐isotope ratios from Tarfaya and portions of the sulphur‐isotope curve from Eastbourne and Raia del Pedale also indicate the probable presence of more oxygen‐rich bottom waters during the Plenus Cold Event. Oxidation by such waters of previously deposited organic‐rich shales, as well as loss of anoxic/euxinic sinks, is credited with temporarily enriching global seawater in a range of other redox‐sensitive trace metals (for example, V, Cr, Co, Ni, Cu, Zn and Cd) during ongoing basalt‐seawater interaction indicated by persistent relatively non‐radiogenic osmium‐isotope seawater values. However, early diagenetic enrichment of manganese in the English Chalk over much of the Oceanic Anoxic Event interval is broadly correlative in time with relatively low osmium‐isotope values in sections elsewhere: a relationship that may be due to the lack of affinity of manganese with carbon‐rich shales, hence allowing relatively elevated concentrations of the element in marine waters to persist during leaching of mafic rocks, unlike other redox‐sensitive species. The calcium‐isotope and lithium‐isotope ratios from Eastbourne and Raia del Pedale indicate an increase in global weathering during the initial phase of Oceanic Anoxic Event 2, and the shift in strontium isotopes and osmium isotopes to more unradiogenic values during the event suggests that not only construction but also destruction of one or more Large Igneous Provinces was probably a proximal cause of this major palaeoceanographic phenomenon by elevating nutrient levels and planktonic productivity in large tracts of the world ocean. Globally widespread carbon burial and silicate weathering are both identified as important mechanisms for drawing down atmospheric carbon dioxide that, in the absence of overwhelming volcanogenic replenishment of this greenhouse gas during the early phase of Oceanic Anoxic Event 2, caused the Plenus Cold Event.